Native T1 Mapping in Assessing Kidney Fibrosis for Patients With Chronic Glomerulonephritis - Wu, Jianhua; Shi, Zhaoyu; Zhang, Yuan; Yan, Jiaxin; Shang, Fangfang; Wang, Yao; Lu, Huijian; Gu, Hongmei; Dou, Weiqiang; Wang, Xinquan; Yuan, Li (Frontiers in Medicine, 2021)
Purpose: To assess the utility of non-contrast enhanced native T1 mapping of the renal cortex in assessing renal fibrosis for patients with chronic glomerulonephritis (CGN). Methods: A total of 119 patients with CGN and 19 healthy volunteers (HVs) were recruited for this study. Among these patients, 43 had undergone kidney biopsy measurements. Clinical information and biopsy pathological scores were collected. According to the results of the renal biopsy, the patients were classified into the high (25–50%), low (<25%) and no renal interstitial fibrosis (IF) (0%) groups. The correlations between the T1 value in the renal cortex and each of the clinical parameters were separately analysed. The relationships between each fibrosis group and the T1 value were also evaluated and compared between groups. Binary logistic regression analysis was further used to determine the relationship between the T1 value and renal fibrosis. Receiver operating characteristic (ROC) curves were plotted to analyse the diagnostic value of the T1 value for renal fibrosis. Results: Compared with those of the HVs, the T1 values were significantly higher in patients at all stages of chronic kidney disease (CKD) (all p<0.05). Significant T1 differences were also revealed between patients with different stages of CKD (p<0.05). Additionally, the T1 value correlated well with CKD stage (p<0.05), except between CKD 2 and 3. In addition, the T1 value was positively correlated with cystatin C, neutrophil gelatinase-associated lipocalin, and serum creatinine and negatively correlated with haemoglobin, kidney length, estimated glomerular filtration rate and haematocrit (all p<0.05). Compared with those of the no IF group, the T1 values were increased in the low- and high-IF groups (both p<0.05). Logistic regression analysis showed that an elevated T1 value was an independent risk factor for renal fibrosis. ROC analysis suggested that the optimal critical value of T1 for predicting renal fibrosis was 1695 ms, with a specificity of 0.778 and a sensitivity of 0.625. Conclusion: Native T1 mapping demonstrated good diagnostic performance in evaluating renal function and was an effective noninvasive method for detecting renal fibrosis in CGN patients.